"Meaningful Human Control in Artificial Intelligence": Practical Dilemmas of the Consensus Principle in Artificial Intelligence - Lin ZOU; Yonghui MA (Yixue yu zhexue, 2025)
The concept of "meaningful human control in artificial intelligence" has been proposed in the context of artificial intelligence (AI) development, emphasizing human oversight over AI systems' autonomous decision-making. While this concept has gradually become a widely accepted guiding principle, it has also sparked a series of controversies. This study traces its conceptual foundations and ethical justifications. It then examines the practical dilemmas of this concept through the case of AI applications in the diagnosis of foraminal stenosis in medicine, exploring under what conditions human control may be appropriately weakened or excluded. Based on this discussion, the paper further explores the ethical principles of human involvement in AI systems, aiming to promote the sustainable development of AI technology.